2012
DOI: 10.3171/2012.8.focus12226
|View full text |Cite
|
Sign up to set email alerts
|

Unusual presentation of congenital dermal sinus: tethered spinal cord with intradural epidermoid and dual paramedian cutaneous ostia

Abstract: The authors present the first report of spinal congenital dermal sinus with paramedian dual ostia leading to 2 intradural epidermoid cysts. This 7-year-old girl had a history of recurrent left paramedian lumbosacral subcutaneous abscesses, with no chemical or pyogenic meningitis. Admission MRI studies demonstrated bilateral lumbar dermal sinus tracts and a tethered spinal cord. At surgery to release the tethered spinal cord the authors encountered paramedian dermal sinus tracts with dual ostia, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…Even paramedian dimples should be examined thoroughly. Cox et al reported a case of a 7-year-old girl with two paramedian dimples and history of recurrent paraspinal soft tissue abscesses managed previously by general surgeons 7. The patient never had meningitis or intradural abscess due to which neurosurgery consultation was deferred.…”
Section: Discussionmentioning
confidence: 99%
“…Even paramedian dimples should be examined thoroughly. Cox et al reported a case of a 7-year-old girl with two paramedian dimples and history of recurrent paraspinal soft tissue abscesses managed previously by general surgeons 7. The patient never had meningitis or intradural abscess due to which neurosurgery consultation was deferred.…”
Section: Discussionmentioning
confidence: 99%
“…The rise of the spinal cord is impeded by an obstructive or a mechanical intradermal anomaly [12]. While split spinal cord syndrome, lipomyelomeningocele, short and thick filum terminale, and adherences second to surgical operations are the most frequent causes of TCS, spinal dermoid cyst and other congenital causes are determined rarely [3, 4, 13, 14]. …”
Section: Discussionmentioning
confidence: 99%
“…Em pacientes assintomáticos, o momento de abordagem cirúrgica é também indefinido, apesar de ser obrigatória a sua realização. (Efrem et al, 2012). Foi demonstrado em alguns estudos que 40% dos diagnósticos de STD são feitos em RM pré-operatória.…”
Section: Relatounclassified